Anti-ribosomal P protein antibodies influence mortality of patients with diffuse psychiatric/neuropsychological syndromes in systemic lupus erythematous involving a severe form of the disease. Issue 4 (4th July 2019) - Arinuma, Yoshiyuki; Kikuchi, Hirotoshi; Hirohata, Shunsei
Abstract: Objectives: The aim of this study is to clarify the effect of various autoantibodies on overall mortality in patients with diffuse psychiatric/neuropsychological syndromes in SLE (diffuse NPSLE). Methods: Fifty-five patients with diffuse NPSLE admitted from 1992 to 2017 had met inclusion criteria and were recruited for this study. The relationship of various serum autoantibodies with mortality was retrospectively analyzed based on the medical charts. Results: Of 55 patients, 14 patients [25.5%] had died during the observation period (2728 [22-8842] days (median [range])). The 5-year, 10-year, 15-year and 20-year mortality rates were 18.8%, 21.9%, 36.9% and 47.4%, respectively. Among various serum autoantibodies at the onset of diffuse NPSLE, only the presence of anti-ribosomal P protein antibodies (anti-ribo P) significantly increased the risk for death (relative risk 2.262, 95% confidence interval 1.276–4.417, p  = 0.005). Of 14 fatal patients, 10 patients had died within 1 y after the onset of diffuse NPSLE. Remarkably, 7 of 10 patients with positive anti-ribo P had died of the severe complication primarily attributed to SLE except for one patient. Conclusions: The presence of anti-ribo P is a significant risk factor for overall poor prognosis in patients with diffuse NPSLE, involving a fatal complication by SLE.